Down the rabbit hole: assessing the influence of schizotypy on the experience of the Barbie Doll Illusion. Issue 5 (3rd September 2018) - Van Doorn, George; De Foe, Alexander; Wood, Alle; Wagstaff, Danielle; Hohwy, Jakob
ABSTRACT: Introduction: "Body swapping" illusions have been used to explore factors contributing to the experience of "owning" an artificial body. Preliminary research indicated that those people diagnosed with schizophrenia experience more vivid illusions of this kind than do "normal" individuals. Objectives: Here, we explored whether participants who rated themselves "high" on the cognitive-perceptual factor of the Schizotypal Personality Questionnaire (SPQ) experienced a more compelling sense of immersion in a variation of the body swapping illusion: The Barbie Doll Illusion. We also hypothesised that these individuals would experience a change in size perception when immersed in the illusion. Method: Forty-four participants wore a pair of Head-Mounted Display goggles connected to a video-camera, and thus a doll's body replaced their own body in their visual field. In two conditions, touch was either applied synchronously or asynchronously to the doll's and each participant's leg. After each condition, participants filled out a questionnaire relating to their experience in the illusion. When both conditions were completed, they filled out the SPQ. Results: Our first hypothesis was confirmed, which suggested that people with higher cognitive-perceptual SPQ scores do indeed experience a more compelling Barbie Doll Illusion; however, our second hypothesis was not supported. Conclusion: Our study demonstrated, for the first time, that proneness to the positive and interpersonal factors of schizotypy in a normal population is sufficient to produce a compelling sense of swapping bodies.